Efek Suplementasi Tepung Semangka dalam Pakan Terhadap Kualitas Interior Telur Ayam Kampung - Nining Haryuni; Syafina Syafi'ina; Anna Lidyawati; - Lestariningsih (LPPM Universitas Nahdlatul Ulama Blitar, 2022)
The purpose of this study was to determine the effect of watermelon seed flour supplementation in feed on the interior quality of native chicken eggs. This research is a biological research using Completely Randomized Design (CRD) with 4 treatments and 5 replications. Each treatment used 5 chickens. The results of statistical analysis showed that watermelon seed flour supplementation in feed had a very significant effect (p<0.01) on the egg yolk index and egg white height and had an insignificant effect (p>0.05) on the egg index. The conclusion of this study is that watermelon seed flour supplementation can improve the interior quality of native chicken eggs. The best supplementation dose at 0.10%.